Neighborhood Effect and Labor Market Integration - Maxime To; Matthieu Solignac (European Regional Science Association (ERSA), 2014)
The 2008 economic crisis raised concerns about unemployment, especially for youths. Over the last decade, two stylized facts can be observed in the French labor market about youth unemployment: its average rate remaining at high levels and its major spatial variations. This paper investigates the impact of neighborhood contexts in getting a job. The identification of these effects from the sorting process requires implementing specific identification strategies. Two complementary approaches are developed in this paper using representative samples of youths leaving the French educational system (Génération 1998 and Génération 2004 panel surveys from the Céreq). In both estimation strategies, the positive impact of local employment conditions on job access remains significant suggesting that the labor market context matters to successfully enter the job market. The results from this study can shed light on the employment gap observed between African immigrants and natives' children in France.
Keywords: R23; J6; J71; Z13; 330